2022
DOI: 10.1038/s41467-022-31207-5
|View full text |Cite
|
Sign up to set email alerts
|

Branched actin networks are organized for asymmetric force production during clathrin-mediated endocytosis in mammalian cells

Abstract: Actin assembly facilitates vesicle formation in several trafficking pathways, including clathrin-mediated endocytosis (CME). Interestingly, actin does not assemble at all CME sites in mammalian cells. How actin networks are organized with respect to mammalian CME sites and how assembly forces are harnessed, are not fully understood. Here, branched actin network geometry at CME sites was analyzed using three different advanced imaging approaches. When endocytic dynamics of unperturbed CME sites are compared, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
1
15
1
Order By: Relevance
“…Increased membrane tension reduces the initiation density ( Ferguson et al, 2017 ), and slows down the growth and dissolution rates of endocytic clathrin-coated structures ( Ferguson et al, 2016 ). Moreover, internalization of CPs from the plasma membrane becomes dependent on the curvature generating adaptor proteins ( Joseph et al, 2020 ; Willy et al, 2021a ) and the forces provided by actin polymerization under increased tension ( Boulant et al, 2011 ; Jin et al, 2022 ; Kaplan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased membrane tension reduces the initiation density ( Ferguson et al, 2017 ), and slows down the growth and dissolution rates of endocytic clathrin-coated structures ( Ferguson et al, 2016 ). Moreover, internalization of CPs from the plasma membrane becomes dependent on the curvature generating adaptor proteins ( Joseph et al, 2020 ; Willy et al, 2021a ) and the forces provided by actin polymerization under increased tension ( Boulant et al, 2011 ; Jin et al, 2022 ; Kaplan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that CCSs on tracks experience a transient period of frustration, as reflected by their longer lifetime, but eventually manage to internalize portions of tracks. Actin has been proposed to be recruited at frustrated CCSs that experience difficulties to bud because of mechanical constraints (Baschieri et al, 2020; Boulant et al, 2011; Jin et al, 2022; Kaksonen et al, 2006; Perrais & Merrifield, 2005). Indeed, we observed that inhibiting actin dynamics with Cytochalasin D resulted in an increased accumulation of stable CCSs along tracks (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…As a first step, we can check simulation times against the physical timescales of the system. Fluctuations of the membrane, with the wave vector q, have a hydrodynamic dissipation timescale of 4η/κq 3 , where η is the viscosity of the solvent and κ ≈ 20 kT is the bending rigidity of the membrane. This gives the hydrodynamic dissipation timescale to be in the 0.01 ms range.…”
Section: Resultsmentioning
confidence: 99%